2013
DOI: 10.1016/j.gaitpost.2013.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered gait termination strategies following a concussion

Abstract: The purpose was to determine if planned gait termination can identify acute and lingering motor control strategy alterations in post-concussion individuals. Controls completed 2 standard gait and 5 planned gait termination trials once while concussed individuals were tested on Day-1 and Day-10 post-concussion. Dependent variables included gait velocity and normalized, relative to standard gait, peak propulsive and braking forces. Control and only Day-1 post-concussion gait velocity differed. Normalized peak pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 15 publications
1
60
0
Order By: Relevance
“…[23] The alterations identified herein may reflect changes in anticipatory postural adjustments (APAs) during planned GT. During a planned action, such as planned GT, the APAs are likely responsible for feedforward neurological control to maintain postural control during the transition from rhythmic gait through movement termination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[23] The alterations identified herein may reflect changes in anticipatory postural adjustments (APAs) during planned GT. During a planned action, such as planned GT, the APAs are likely responsible for feedforward neurological control to maintain postural control during the transition from rhythmic gait through movement termination.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Indeed, in a preliminary study, Buckley et al identified an altered propulsive and braking force motor strategy following concussion during planned GT. [23] Specifically, this strategy presented independent of gait velocity and persisted beyond clinical recovery (e.g., self-reported symptoms, computerized neurocognitive testing, and clinical cognitive/balance exams), suggesting a persistent deficit at least 10 days post-concussion; however that study was cross-sectional as baseline data was not presented. [23] Conversely, herein these findings identify alterations both within participants, as compared to healthy baseline performance, as well as to a healthy athletic population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurobiological supporting evidence potentially linking psychological outcomes with chronic post-concussion alterations include both altered frontal-alpha symmetry on EEG assessment and dorsolateral prefrontal cortex connectivity, which have been associated with the neural substrates underlying psycho-affective health (Chen et al, 2008; Moore, Sauve, & Ellemberg, 2016; van der Horn et al, 2016). Interestingly, postural control testing of gait termination, a functional task with dorsolateral prefrontal cortex supraspinal control, has identified deficits post-concussion which provides further potential evidence linking the systems (Buckley, Munkasy, Tapia-Lovler, & Wikstrom, 2013; Oldham, Munkasy, Evans, Wikstrom, & Buckley, 2016). An emerging area of concussion research suggests an elevated risk of post-concussion subsequent MSK injury in collegiate student-athletes (Brooks et al, 2016; Gilbert, Burdette, Joyner, Llewellyn, & Buckley, 2016; Lynall, Mauntel, Padua, & Mihalik, 2015) and both impaired postural control and residual psychological disturbances have been speculated as potential confounders or mechanisms.…”
Section: Discussionmentioning
confidence: 99%